Pengaruh Kualitas Produk, Price fairness, Citra Merek dan Kepercayaan Merek Terhadap Kepuasan Pelanggan Handphone Merek Samsung di Banjarmasin - Abul Hasan Asy’ari; Anthonius Junianto Karsudjono (Al-KALAM : JURNAL KOMUNIKASI, BISNIS DAN MANAJEMEN, 2021)
This study aims to determine the effect of Product Quality, Price Fairness, Brand Image, and Brand Trust variables on Customer Satisfaction of Samsung brand mobile phones. This research is a correlational study with the population is all people who own and use Samsung mobile phones that meet the requirements for respondents. The sample in this study was 125 respondents. The results showed that (1). Simultaneously the Product Quality, Price Fairness, Brand Image and Brand Trust variables significantly influence Customer Satisfaction (2). Partially, Product Quality and Price Fairness variables have no significant effect on Customer Satisfaction. Whereas the Brand Image variable, Brand Trust has a significant effect on Customer Satisfaction.